Mlokorejo Islamic Boarding School and the Ecotheology of Crisis: Challenging Religion's Silence on Environmental Destruction - Muzammil, Moh; M Khoirul Hadi Al Asy'Ari (Yayasan Dinamika Ilmu Banyuwangi, 2025)
The increasing complexity of the ecological crisis requires active engagement from various institutions, including Islamic educational institutions such as pesantren, in fostering environmentally responsible behavior grounded in religious values. This study aims to analyze the role of Bustanul Ulum Mlokorejo Islamic Boarding School in responding to the ecological crisis and to examine the integration of Islamic values in shaping ecotheological awareness within the pesantren environment. This research employs a qualitative descriptive approach. Data were collected through participant observation, in-depth interviews with pesantren administrators, kyai, and students, as well as document and literature analysis. The data were analyzed using thematic analysis to identify patterns in the integration of religious values and ecological practices. The findings reveal that the pesantren has implemented several environmentally oriented practices, including waste management, routine communal work, independent water resource utilization, and reforestation initiatives. These practices reflect the emergence of ecological awareness rooted in Islamic values such as tauhid (oneness of God), khalifah (stewardship), amanah (trust), tawazun (balance), zuhud (simplicity), and the prohibition of fasad (destruction). However, the integration of these values remains largely implicit and has not yet been formally institutionalized within the curriculum or governance system. Furthermore, limited environmental literacy, resource constraints, and the absence of structured policies constitute major challenges in strengthening the role of pesantren as centers of ecotheological education. This study contributes to the development of Islamic ecotheology by emphasizing the importance of integrating religious values with institutional management systems in fostering sustainable ecological awareness. It also offers practical implications for developing a more systematic and structured ecotheology-based pesantren model that is responsive to contemporary environmental challenges.